1994
DOI: 10.1161/01.hyp.23.5.607
|View full text |Cite
|
Sign up to set email alerts
|

Sex influence on renal alpha 2-adrenergic receptor density in the spontaneously hypertensive rat.

Abstract: Male spontaneously hypertensive rats (SHR) have higher blood pressure than females. We compared renal ct 2 -adrenergic receptor density among intact SHR and Wistar-Kyoto (WKY) rats of both sexes, male and female SHR gonadectomized at 4 weeks of age, and gonadectomized SHR supplemented with testosterone. Additional groups of SHR were treated with enalapril (30 mg/kg per day), an angiotensinconverting enzyme inhibitor, from 5 to 14 weeks of age. Renal a 2 -adrenergic receptor density was higher in males than fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
17
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 30 publications
(35 reference statements)
4
17
2
Order By: Relevance
“…Although gender has been shown to influence the status of hypertension in other rat models of the disease [1][2][3], the present study is the first to demonstrate an influence in the 2K1C model. In this study, male 2K1C rats were nearly twice as likely to develop hypertension compared with their female counterparts.…”
Section: Discussioncontrasting
confidence: 56%
“…Although gender has been shown to influence the status of hypertension in other rat models of the disease [1][2][3], the present study is the first to demonstrate an influence in the 2K1C model. In this study, male 2K1C rats were nearly twice as likely to develop hypertension compared with their female counterparts.…”
Section: Discussioncontrasting
confidence: 56%
“…Although the mechanisms responsible for the gender differences in hypertension are not clear, there is significant evidence that androgens such as testosterone play an important role in the gender-specific blood pressure regulation (Reckelhoff, 2001). Indeed, hypertension was reduced by castration in SHR and in Dahl and Sabra salt-sensitive rats (Crofton et al, 1993;Gong et al, 1994;Khalid et al, 2001). Furthermore, administration of androgen receptor antagonist, for 10 days after birth, attenuates the hypertension of male adult SHR, whereas neonatal androgenization of female SHR leads to similar hypertension as that in male (Cambotti et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ␣ 2B -adrenoceptor densities were markedly increased by the high salt diet. These high levels, which appear to be the consequence of an overexpression of the encoding gene, have also been observed in SHR rats (Gong et al, 1994(Gong et al, , 1995. However, the ␣ 2A -adrenoceptor mRNA was clearly present in kidneys of intact SBH rats under both normal and high salt diet.…”
Section: Discussionmentioning
confidence: 55%
“…Surprisingly, none of the studies mentioned above dealing with the importance of renal ␣ 2 -adrenoceptors in the development of hypertension have considered the possible role of sex. More recently, however, it has been demonstrated that both renal ␣ 2 -adrenoceptor density and blood pressure are influenced by sex in SHR and Wistar Kyoto rats (Gong et al, 1994). In this latter study, it was shown that androgens are needed for the full expression of hypertension as well as for the increase of renal ␣ 2 -adrenoceptor density in SHR rats.…”
mentioning
confidence: 74%
See 1 more Smart Citation